Context sensitive policy instruments: A multi-criteria decision analysis for safeguarding forest habitats in Southwestern Finland. (March 2020) - Sironen, Susanna; Primmer, Eeva; Leskinen, Pekka; Similä, Jukka; Punttila, Pekka
Highlights: Four policy instruments to safeguard biodiversity were compared after a 20-year time period. Multiple data sources, spatial analysis and Multi-Criteria Decision Analysis were applied. Voluntary permanent conservation supplemented with temporary conservation is recommended. No rationale for enforced spatially concentrated permanent conservation instead of voluntary conservation instruments. Abstract: Environmental and conservation decisions are often complex, which results in complexity also in policy assessments. Conservation decisions have implications for different stakeholders and typically draw on multidisciplinary knowledge bases, incorporating natural, physical and social sciences, politics and ethics. Multi-Criteria Decision Analysis (MCDA) is a potentially important tool for supporting conservation policy decisions. This article reports a spatially referenced MCDA of policy instrument scenarios for conserving forest biodiversity in Southwestern Finland. The effects of the realistic policy instruments designed in dialogue with stakeholders included voluntary permanent conservation, enforced spatially concentrated permanent conservation, voluntary permanent conservation with active nature management, and voluntary temporary conservation. These instruments were compared by combining forest-owner survey, MCDA and ex ante impact evaluation. The main objective was to find the forest biodiversity conservation instrument that would produce the highest total benefit. The effects of the different instruments were evaluated with ecological, economic, social, and institutional criteria after a 20-year time period. The results showed minor differences between the instruments, with voluntary permanent and voluntary temporary conservation producing the largest total benefit. Despite the small differences, the analysis was robust in showing that voluntary instruments were more favourable than enforced permanent conservation.